Emerging Role of Microtubule-Associated Protein 2 as a Prognostic Factor for Renal Dysfunction - Talab, Fatima Ghazi; Ahmed, Hind Shakir (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Chronic kidney disease (CKD) is a severe medical disorder manifested by a decline in kidney function over an extended period. This leads to the accumulation of toxins and the gradual inability to remove excess waste and fluids from the body. Microtubule-associated protein 2 (MAP2) is part of a protein family that regulates microtubule structure and cellular metabolism. This study aims to analyze the effectiveness of these parameters in evaluating CKD and its associated mechanisms in Iraqi patients. The study was conducted from December 2023 to May 2024. Ninety subjects enrolled in this study: 60 patients with CKD who attended the Baghdad Teaching Hospital/Medical City/ Dialysis Unit in Baghdad, Iraq. Additionally, 30 healthy subjects were designated as the control group. Their ages ranged from 48 to 65 years. The present results indicated significantly higher serum MAP2 levels in CKD patients undergoing dialysis as compared to the control (616.10±12.25 vs. 125.48±10.14) ρg/mL. In addition, the present results revealed a significant positive correlation between serum MAP2 and levels of various parameters, including fasting glucose, lipid profile, and renal function tests. A significant negative correlation exists between serum MAP2 levels and serum total protein, albumin, and estimated glomerular filtration rate. It was found that higher levels of serum MAP2 in hemodialysis patients reveal their critical role in renal dysfunction. Therefore, this factor may serve as a biomarker of kidney injury progression among patients with CKD.